Speed and Lane Change Characteristics of Motorcycles at Priority Junction - Benidiktus Susanto; Siti Malkhamah; Latif Budi Suparma; Arumdyah Widiati (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2026)
Motorcycles are Indonesia’s predominant mode of transportation and contribute to a substantial share of road traffic accidents. The research aims to identify key behavioural factors contributing to motorcycle-related conflict risks at intersections and to propose evidence-based safety interventions. This study analyzed speed characteristics with varying degrees of disruption that motorists would experience at the intersection. These disruptions were categorized into high, low, no disruption, and left-turn movements. High disruption was defined as vehicles stopping in the middle of the intersection as motorcyclists approached, while low disruption was defined as vehicles preparing to enter the intersection from minor roads. In addition to speed characteristics, this study also observed lane-changing behavior when disruptions occurred at the intersection. To obtain detailed data, drone-based cameras were used for observations, and the results were validated against radar speed measurements. The results show that 67.94% of riders exceed the 60 km/h speed limit during the morning period, while 33.27% exceed it in the afternoon, indicating clear temporal differences in operating speeds. Approximately 85 per cent of lane-changing manoeuvres occur within 20 metres of the conflict point, reflecting short decision distances that increase collision risk. Riders also exhibit assertive gap-acceptance behaviour, often requiring main-road vehicles to adjust their speed. Statistical validation confirms that there is no significant difference between drone-derived and radar-based speed measurements, demonstrating the reliability of the drone-based methodology. Based on these findings, the study recommends targeted speed management measures, including automated enforcement and the use of traffic-calming devices; improved lane discipline through more precise road markings and selective physical separation; and junction design enhancements, such as motorcycle waiting areas and advanced stop lines. These measures can improve motorcycle safety at priority junctions and support more efficient and predictable urban traffic operations.